Potential roles of microRNA in levonorgestrel-treated uterine leiomyoma cells - Ma, Huiyuan; Shi, Xiaoyan; Fu, Ziyi; Wu, Xiaoli; Huangfu, Yushuang; Xu, Pengfei; Zeng, Xin; Xu, Juan; Ruan, Hongjie; Xu, Qing (Translational Cancer Research; Vol 7, No 6 (December 30, 2018): Translational Cancer Research, 2018)
Background: Uterine leiomyoma is a common, benign, female tumor, which leads to gynecological disorders such as a recurrent pregnancy loss, and menstrual abnormalities. Although uterine leiomyoma can be cured by surgical and partial endocrine therapy, little is known about the biological mechanisms. Methods: In this study, uterine leiomyoma cells were treated with levonorgestrel (LNG) and prepared for microRNA (miRNA) microarray assay. The de-regulated miRNAs detected by microarray were confirmed by a quantitative polymerase chain reaction (qPCR). Gene ontology and pathway analysis were carried out to investigate the biological functions of these dys-regulated miRNAs. Results: The microarray data discovered 9 significantly up-regulated miRNAs and 32 predominantly down-regulated miRNAs in LNG-treated uterine leiomyoma cells. qPCR results further validated these discoveries. Gene ontology annotation showed that these dys-regulated miRNAs could regulate cell bicarbonate transport, phosphoinositide 3-kinase cascade, and other biological processes. Meanwhile, pathway analysis demonstrated that these dys-regulated miRNAs might participate in ErbB-MAPK signaling pathway regulation. Conclusions: The above results suggest that these dys-regulated miRNAs probably play a critical role in the progression of uterine leiomyoma. By providing new glimpses into the molecular mechanisms underlying the LNG intrauterine system (LNG-IUS) remedy, our study might be helpful in developing noninvasive clinical treatment for uterine leiomyoma.